The role of psycho-emotional factors in assessing the prognosis of different types of myocardial infarction - V. I. Kinash; V. V. Kashtalap; A. S. Vorobiev; I. A. Urvantseva; L. V. Kovalenko (Российский кардиологический журнал)
Aim. To study the features of psycho-emotional status and its clinical and prognostic significance in patients with type 1 and 2 myocardial infarction (MI).Material and methods. Of the 1293 patients hospitalized at the District Cardiology Dispensary "Center for Diagnostics and Cardiovascular Surgery" with a diagnosis of acute coronary syndrome, 277 (21,4%) patients with confirmed MI were consecutively included in the observational study. There were 194 (15,0%) patients with type 1 MI (MI1) and 83 (6,4%) with type 2 MI (MI2). MI types were determined based on the IV Universal Definition of Myocardial Infarction (UDMI). During the hospital period, type D personality was identified using the Russian version of the Type D scale-14 (DS-14), while the presence and severity of anxiety and depression was assessed using the Hospital Anxiety and Depression Scale (HADS). Follow-up was conducted through outpatient visits, telephone or email interviews for 12 months after discharge. Patients' adherence to drug therapy was assessed using 8-item Morisky Medication Adherence Scale, and quality of life (QoL) using Short Form Medical Outcomes Study (SF-36) questionnaire.Results. During the hospital period, in the group of patients with MI2, patients with type D personality were more often identified compared with MI1 (30 (36,1%) vs 55 (28,3%), p<0,05). Patients with MI2 had a significantly higher subclinical level of anxiety (34 (41,0%) vs 43 (22,2%), p=0,002), expressed level of anxiety (10 (12,1%) vs 12 (6,2%), p=0,011), as well as a significant level of depression (13 (15,7%) vs 14 (7,2%), p=0,03). At the same time, in patients with type D, regardless of MI type, subclinical levels of anxiety and depression were significantly expressed (63 (74,1%) vs 14 (7,3%) (p<0,001) and 58 (68,2%) vs 25 (13,0%) (p<0,001)). There were no significant differences in inhospital complications between the MI1 and MI2 groups depending on type D personality. After 12-month follow-up, patients with the distressed personality type had higher rate of all-cause death (5 (7,2%) vs 5 (1,6%), p<0,05 without type D), rehospitalization for decompensated heart failure (8 (11,5%) vs 9 (4,8%), p=0,04). Patients with type D were less adherent to drug therapy compared to patients without type D (30 (43,4%) vs 9 (4,8%) p=0,001, respectively), and they had lower QoL scores.Conclusion. Type D personality, the presence of anxiety and depression, high all-cause mortality and rehospitalization rate of decompensated heart failure were more often observed in MI2 compared to MI1, as well as in patients with type D, regardless of MI type. Low adherence to drug therapy and poor quality of life, regardless of MI type, were also associated with the type D personality.